tipificar como infracción en el Código Orgánico Integral Penal el daño psicológico por discriminación - Guerra Gamboa, Mayra Adela (2017)
This research work whose theme is "establish as VIOLATION IN THE COMPREHENSIVE ORGANIC PENAL CODE THE PSYCHOLOGICAL DAMAGE DISCRIMINATION" Thus the aim of this research is aimed to create a policy that seeks to establish access of psychological damage within the Comprehensive Organic Penal code, to not violate Constitutional rights and a level playing field is established that the rest of the people. Current legislation in Ecuador expected within the fifth section of the second chapter crimes against the right to equality to the people among whom only typify discrimination I acts of hatred, although these two offenses punishable ducts concerning discrimination and acts of hatred, they by no means cover in full all the fraudulent actions that the effect of discrimination cause serious damage to their victims especially in the psychological aspect. As it is known Ecuador is a multicultural and multiethnic country which may lead to a great amount of ethnic and cultural makeup in confined spaces which has led over time to give a great fight between these and serious effects mainly in one psychological level in people, which our criminal law Ecuadorian not expected nor sanctioned, is why the research will be placed on identifying the problems that causes the lack of these regulations, knowing that the damage caused to the victim is irreparable and taking into consideration that constitutional rights and guarantees are violated by discrimination either because of ethnic culture, social status, etc. and affect the victim with a very serious I irreparable psychological problem within their social life. This thesis Legal Research is structured as follows: First a Conceptual Framework, comprising concepts and definitions, as have the psychological damage is the main theme of our research, as well as other concepts that will enhance the visibility of the proposed topic; doctrinaire framework, covering the doctrines of writers and scholars on how you can set a penalty to punish the aggressor who commits psychological damage and a legal framework, which includes the analysis of the Constitution of the Republic of Ecuador, the Organic Code Criminal Integral as well as other legal bodies and then we have a comparative legislation because it helped me to make an analysis of matter from other countries and to extract the most positive. Secondly the research work includes a field study in which surveys and interviews are developed connoisseurs of law in helping me determine or contrast the objectives and hypotheses raised. Third after the analysis of field research we proceeded to the conclusions and recommendations and finally to a legal proposal necessary for the solution of the problem.